Maternal mortality, Arzobispo Loayza National Hospital. 2000-2004 - Izaguirre, Mariela (2015)
OBJETIVE: To determine the rate of hospital maternal mortality as well as the most frequent causes. DESIGN: Retrospective, descriptive, cross-sectional study. MATERIALS AND METHODS: Fifty-three cases of maternal death in the Archbishop Loayza (HNAL), general hospital and reference National Hospital, between January 1994 and December 2004. RESULTS: The maternal mortality rate between January 1994 and December 2004 was 115.4 per 100 000 nv. The annual death rate was 4.8. The most frequent age was between 30 and 40 years, with 22.6%. There were no maternal deaths in children younger than 15 and older than 45 years. The deaths were more frequent in the postpartum period, with 71.7%. Predominated direct cause deaths, with 64.2%, the main infection (30.2%), hypertension (26.4%) and bleeding (7.5%). Direct causes include septic abortion and eclampsia, with 26.5% each. Over the past five years, 64% of the deaths were preventable. CONCLUSIONS: The maternal mortality rate in our institution between 1994 and 2004 was low compared with other national hospitals. The main cause of death is direct, which coincides with most national reports and developing countries.